Receptor-binding domain of SARS-Cov spike protein: Soluble expression in E.coli, purification and functional characterization - Chen, Jing (World J Gastroenterol, 2005)
AIM: To find a soluble and functional recombinant receptor-binding domain of severe acute respiratory syndrome-associated coronavirus (SARS-Cov), and to analyze its receptor binding ability. METHODS: Three fusion tags (glutathione S-transferase, GST; thioredoxin, Trx; maltose-binding protein, MBP), which preferably contributes to increasing solubility and to facilitating the proper folding of heteroprotein, were used to acquire the soluble and functional expression of RBD protein in Escherichia coli (BL21(DE3) and Rosetta-gamiB(DE3) strains). The receptor binding ability of the purified soluble RBD protein was then detected by ELISA and flow cytometry assay. RESULTS: RBD of SARS-Cov spike protein was expressed as inclusion body when fused as TrxA tag form in both BL21 (DE3) and Rosetta-gamiB (DE3) under many different cultures and induction conditions. And there was no visible expression band on SDS-PAGE when RBD was expressed as MBP tagged form. Only GST tagged RBD was soluble expressed in BL21(DE3), and the protein was purified by ÄKTA Prime Chromatography system. The ELISA data showed that GST.RBD antigen had positive reaction with anti-RBD mouse monoclonal antibody 1A5. Further flow cytometry assay demonstrated the high efficiency of RBD's binding ability to ACE2 (angiotensin-converting enzyme 2) positive Vero E6 cell. And ACE2 was proved as a cellular receptor that meditated an initial-affinity interaction with SARS-Cov spike protein. The geometrical mean of GST and GST.RBD binding to Vero E6 cells were 77.08 and 352.73 respectively. CONCLUSION: In this paper, we get sufficient soluble N terminal GST tagged RBD protein expressed in E.coli BL21(DE3); data from ELISA and flow cytometry assay demo-nstrate that the recombinant protein is functional and binding to ACE2 positive Vero E6 cell efficiently. And the recombinant RBD derived from E.coli can be used to developing subunit vaccine to block S protein binding with receptor and to neutralizing SARS-Cov infection.